878 Comparing Treatment Outcomes for Unruptured Brain Arteriovenous Malformations: A Retrospective Cohort Study. (4th May 2021) - Taweel, B; Gillespie, C; Ali, T; Islim, A; Hannan, C; Chavredakis, E
Abstract: Background: Unruptured brain arteriovenous malformations (bAVMs) carry a lifetime risk of haemorrhage. Treatment strategies include conservative management, microsurgical excision, endovascular treatment (EVT) and radiosurgery (SRS). Optimal treatment selection remains unclear. Method: A single-centre retrospective cohort study of adult unruptured bAVMs (2007-2019). Patients who underwent intervention were propensity matched using baseline features (age, sex, size, deep drainage, eloquence, and Spetzler-Martin grade) with patients conservatively managed. Rates of neurological disability and mortality due to intervention or bleed were compared. Results: 137 patients (mean age 48 years [SD = 16], males 64) were included; 34 (25%) EVT, 20 (15%) surgery, 31 (22%) SRS and 51 (37%) conservative. After a median follow-up of 49 months (IQR 23-75), rates of disability were as follows: surgery 35%, EVT 21%, SRS 13% and conservative 8%. Matched cohorts (intervention/conservative) were: surgery-19/18, SRS-30/22 and EVT-33/34. Comparison of disability rates across matched cohorts revealed no statistically significant differences (surgery p = 0.07, SRS p = 0.65 and EVT p = 0.11). Three conservatively managed patients died. Conclusions: Unruptured bAVMs carry a significant risk of neurological morbidity, regardless of intervention choice. Treatment choice may have an impact on patient outcomes but requires investigation of stratified cohorts. Findings are consistent with the nuances of AVM treatment selection.